Penggunaan Aplikasi Wordwall dalam Evaluasi Pembelajaran Bahasa Indonesia Siswa Sekolah Dasar - Galih Maulana Hendrawan; Dien Nurmarina Malik Fadjar (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This paper aims to evaluate the effectiveness of using the Wordwall application in learning Indonesian for elementary school students. Wordwall is a digital platform based on educational games that allows teachers to create interactive learning activities online and offline. The research method used is classroom action with two cycles, where each cycle includes the planning, implementation, and evaluation stages. The results of the study indicate that the use of Wordwall can increase student interest, motivation, and engagement during learning. This application helps teachers in delivering material in a fun way, and is able to encourage active student participation in the learning process. Thus, Wordwall is proven to be an effective and relevant learning media to be applied in teaching Indonesian at the elementary school level.